Employers’ Perception of the Impact of Artificial Intelligence on Talent Acquisition in LATAM - Lozano, Jorge H (Digital Repository of Theses - SSBM Geneva, 2024)
The utilization of artificial intelligence (AI) in business has significantly influenced the manner in which companies operate and has had a profound effect on the talent acquisition process. AI technology has enabled firms to enhance their operational efficiency, cost-effectiveness, and decision-making capabilities. The advent of AI has created new avenues for organizations to identify, evaluate, and hire top talent more swiftly and effectively. This dissertation will examine the perspectives of employers on the impact of AI on talent acquisition methods in Latin America. The research design utilized in this study is rooted in the positivist paradigm and employs a quantitative research method. The approach taken in this study is to use structural equation modeling (SEM) to create a model that predicts the relationships between various variables. The study revealed a robust correlation between HR managers' perceptions of the utility of AI in enhancing the efficiency of the talent acquisition process and their attitudes and intentions regarding the deployment of AI. The research also indicated that HR managers' perceptions exert a considerable influence on their opinions, attitudes, and intentions vis-a-vis the employment of AI in the hiring process. The study further demonstrated that the level of conviction of HR managers that utilizing AI will contribute to efficiency in talent acquisition is significantly and positively associated with their feelings about the use of AI for talent acquisition and the degree of willingness of HR managers to use AI for talent acquisition. Overall, the research underscores the need to take into account HR managers' attitudes and views when implementing AI in talent acquisition procedures in LATAM countries.